Barriers of delivering oral health care to older people experienced by dentists: a systematic literature review. Issue 2 (18th September 2013) - Bots‐VantSpijker, Pieternella C.; Vanobbergen, Jacques N.O.; Schols, Jos M.G.A.; Schaub, Rob M.H.; Bots, Casper P.; de, Cees
Abstract Objective To identify barriers of delivering oral health care to older people experienced by dentists. Methods A comprehensive literature search was carried out for studies published in the period January 1990–December 2011, using free text and MESH term search strategies for PubMed (Medline), EMBASE and CINAHL. Results The initial search identified 236 potentially relevant publications: PubMed (Medline; n = 127), EMBASE (n = 108) and CINAHL (n = 1). After screening of titles and abstracts, 14 publications were revealed as relevant for further review. Seven articles, focusing on dentists delivering oral health care to older people in care homes, were suitable for this review, and seven articles did not meet the previously determined quality criteria. One of these articles also focused on barriers experienced by dentists working in their own practice and delivering oral health care to community‐dwelling older people. Conclusions The most common barriers of delivering oral health care to older people were identified respectively as: the lack of adequate equipment in a care home and no area for treatment available (n = 4) and the lack of adequate reimbursement for working in a care home (n = 5). In addition, the inadequate training and experience in delivering oral health care to older care home residents (n = 2) were mentioned. Four publications indicated the loss of time from private practice as a barrier to deliver oral health care in a care home. We suggest that additional research should be initiated to investigate more in detail the barriers dentists experience in delivering oral health care to older people in their own dental practices.